Successful Anesthetic Management of Pheochromocytoma in a Patient with Preoperative Hypertension: A Case Report - Faisal Irwanda; Novita Anggraeni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Pheochromocytoma, a rare tumor arising from chromaffin cells in the adrenal medulla, poses significant anesthetic challenges due to its propensity to release catecholamines, potentially leading to life-threatening hypertensive crises. This case report describes the successful anesthetic management of a patient with pheochromocytoma presenting with preoperative hypertension. Case presentation: A 37-year-old female with a 12x5 cm right adrenal tumor diagnosed as pheochromocytoma was scheduled for adrenalectomy. She presented with a history of uncontrolled hypertension, episodic headaches, diaphoresis, and palpitations. Preoperative management focuses on blood pressure control using alpha and beta-adrenergic blockers. Anesthesia was induced with propofol, fentanyl, and atracurium, while nitroglycerin and sevoflurane were used to maintain hemodynamic stability. The patient's blood pressure was closely monitored throughout the procedure, with interventions made to manage fluctuations during tumor manipulation. Conclusion: Successful anesthetic management of pheochromocytoma requires meticulous preoperative preparation, vigilant intraoperative monitoring, and prompt pharmacological interventions. This case highlights the importance of a multidisciplinary approach, including endocrinologists, anesthesiologists, and surgeons, to optimize patient outcomes.